Protecting trade secrets as a part of a successful business strategy - Aakula, Kalle (My University, 2020)
I will concentrate on comparing the trade secret laws of the United States and the European Union between each other in the research. More specifically comparisons will be made be-tween the laws of the state of California and Finland in relation to trade secret laws. The purpose of the research is to point out differences and also to find out similarities between the respective judicial systems. The main analysis of trade secret laws will be made from the perspective of companies but aspects that relate to employee mobility will also be con-sidered when deemed appropriate to reflect the different interests that relate to trade se-cret laws. The objective of the research is to create value for companies that aim at protecting their trade secrets as a part of a successful business strategy. Primarily it will be evaluated that how companies can avoid situations where trade secret protection is not granted to them and how companies can avoid situations where their trade secrets are misappropriated. Plenty of court cases will be considered as a part of this research and the relevance of those cases will be analyzed. The enforceability of contracts is also one of the fundamental as-pects that will be considered in this research because the respective jurisdictions have dif-ferences that have an impact on trade secret protection strategies. I conclude my research by comparing the most important aspects of the trade secret laws between these judicial systems. Additionally, the conclusion chapter will be dedicated to analyzing ways that how trade secret legislation could evolve in the future in order to ad-vance cross-border innovation and dissemination of information further.

Keskityn tutkielmassani vertailemaan Yhdysvaltojen ja Euroopan Unionin liikesalaisuus-lainsäädäntöjä keskenään. Tutkielmassa keskitytään etenkin vertailemaan Suomen ja Kalifornian osavaltion lainsäädäntöjä. Tarkoituksena on primäärisesti arvioida vallitsevia eroja mutta myös yhtäläisyyksiä oikeusjärjestelmien välillä. Liikesalaisuuslakeja vertail-laan pääasiassa yritysten näkökulmat huomioon ottaen. Työssä pohditaan myös aiheelli-silta osin työntekijöiden vapaan liikkuvuuden turvaamiseen tarvittavia intressejä liikesa-laisuuksien turvaamiseksi, jotta liikesalaisuuslakien eri näkökulmat tulevat huomioon otetuksi. Työn tarkoituksena on tuottaa lisäarvoa yrityksille, jotka pyrkivät suojaamaan liikesalai-suuksiaan mahdollisimman tehokkaasti osana menestyksekästä yritysstrategiaa. Työssä keskitytään pääasiassa osoittamaan millä keinoin yritykset pystyvät suojaamaan liikesa-laisuuksiaan ja välttämään aiheettomia liikesalaisuuksiin liittyviä loukkauksia, joita työn-tekijät taikka kolmannet osapuolet saattavat aiheuttaa. Tutkielmassa analysoidaan lu-kuisia oikeustapauksia ja arvioidaan niiden merkitystä. Sopimusten täytäntöönpano on myös fundamentaalinen aspekti, jota analysoidaan, sillä analysoitavien oikeusjärjestel-mien välillä on eroja, joilla on vaikutuksia liikesalaisuuksien suojaamiseen liittyen. Päätän tutkielmani esittämällä yhteenvedon työssä käymistäni asioista vertaamalla oi-keusjärjestelmiä keskenään. Tutkielman lopussa pohditaan, miten liikesalaisuuslakeja voitaisiin edelleen kehittää siten, että innovaatiohankkeet ja tiedon välittäminen lisään-tyisivät maiden välillä.
Keywords: Trade secret, non-disclosure agreement, non-compete agreement, skills and knowledge of employees, loyalty obligation, reasonable steps